Using Free Writing Technique by Peter Elbow to Increase Students’ Competence in Arabic Writing - Makhisoh, Iis (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2020)
Being afraid of making linguistic errors and feeling hard to express ideas made students of Madrasah Aliyah Negeri 3 Jombang think that writing is difficult. Therefore, they are poor in writing. That is why this classroom action research was conducted. This research was done in three cycles. The implementation of teaching-learning activity by using free writing runs well. The students’ competence in writing in all cycles increased after using free writing technique. Therefore, there is significance relation between using free writing technique and the improvement of students skill in writing.